2020
DOI: 10.3390/foods9111590
|View full text |Cite
|
Sign up to set email alerts
|

Unripe Black Raspberry (Rubus coreanus Miquel) Extract and Its Constitute, Ellagic Acid Induces T Cell Activation and Antitumor Immunity by Blocking PD-1/PD-L1 Interaction

Abstract: Rubus coreanus Miquel (R. coreanus) is a unripen fruit of black raspberry native to eastern Asia. It is used as traditional oriental medicine and supplementary foods for centuries. Previous studies have shown that the R. coreanus extract (RCE) and its main constitute ellagic acid possess diverse biological activities. However, the effects of RCE on antitumor immunity and T cell function were not fully understood. The present study describes the anti-tumor effect of RCE in humanized PD-1 mice by blocking PD-1/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Moreover, the MC38 used in vivo in this study is derived from tumors induced by carcinogen and established in C57BL/6 mice and represents a microsatellite-unstable CRC cell line ( 31 ). We have previously reported the PD-1/PD-L1-inhibiting abilities of medicinal herbs including Salvia plebeia alone and Rubus coreanus alone in vivo ( 20 , 32 ). Here, we found that SRE in combination with anti-PD-1 antibodies in vivo is a potent PD-1/PD-L1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the MC38 used in vivo in this study is derived from tumors induced by carcinogen and established in C57BL/6 mice and represents a microsatellite-unstable CRC cell line ( 31 ). We have previously reported the PD-1/PD-L1-inhibiting abilities of medicinal herbs including Salvia plebeia alone and Rubus coreanus alone in vivo ( 20 , 32 ). Here, we found that SRE in combination with anti-PD-1 antibodies in vivo is a potent PD-1/PD-L1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that a black raspberry ( Rubus coreanus Miquel) extract (RCE) interrupted the binding of PD-1 and PD-L1 with an IC 50 value of 83.8 ± 4.7 μg/mL in the competitive ELISA assay [ 118 ]. PD-L1 aAPC/CHO-K1 cell co-culture based assay revealed that RCE increased the production of IL-2 by 1.8-fold with an EC 50 value of 56.15 ± 14.35 μg/mL, as compared to the control group.…”
Section: Natural Product-derived Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%
“…Ellagic acid was shown to block PD-1/PD-L1 interaction in a concentration-dependent manner with an IC 50 value of 22.92 μg/mL (Table 1 ). In addition, ellagic acid-conjugated sepharose 4B beads pull-down assay showed that ellagic acid was able to directly bind PD-1 and PD-L1 and interrupt their binding capacity [ 118 ].…”
Section: Natural Product-derived Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%
“…Based on ethnopharmacological information, our previous hepatoprotective experiments, 15 and the reported antioxidant and anti-inflammatory effects and safety data, we selected 12 Korean medicinal herbs: soybean sprouts, 16,17 Oenanthe javanica (Blume) DC., 18 immature Citrus reticulata Blanco peel, 19 Hovenia dulcis Thunb., 20,21 immature Rubus coreanus Miq., 22,23 Artemisia capillaris Thunb., 24 Chaenomeles sinensis (Dum. Cours.)…”
Section: Introductionmentioning
confidence: 99%
“…Potent anti-ulcer agents used in traditional Korean medicine approaches that have strong antioxidant effects, such as Artemisia asiatica extract (Stillen Ô , Dong-A Pharmaceuticals, Korea), are also commercially available. 14 Based on ethnopharmacological information, our previous hepatoprotective experiments, 15 and the reported antioxidant and anti-inflammatory effects and safety data, we selected 12 Korean medicinal herbs: soybean sprouts, 16,17 Oenanthe javanica (Blume) DC., 18 immature Citrus reticulata Blanco peel, 19 Hovenia dulcis Thunb., 20,21 immature Rubus coreanus Miq., 22,23 Artemisia capillaris Thunb., 24 Chaenomeles sinensis (Dum. Cours.)…”
Section: Introductionmentioning
confidence: 99%